2018
DOI: 10.1016/j.aap.2018.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Young drivers’ perception of adult and child pedestrians in potential street-crossing situations

Abstract: Despite overall improvements in road traffic safety, pedestrian accidents continue to be a serious public health problem. Due to lack of experience, limited cognitive and motoric skills, and smaller size, children have a higher injury risk as pedestrians than adults. To what extent drivers adjust their driving behaviour to children's higher vulnerability is largely unknown. To determine whether young male drivers' behaviour and scanning pattern differs when approaching a child and an adult pedestrian in a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…On the part of human factors, Wu and Xu [21] and Abele et al [22] highlighted that driver behaviors such as speeding, drunk-driving, fatigue, safety measures adopted, and risktaking behaviors are the most influential causes of traffic-related causalities. Febres et al [23] blamed young drivers for risky driving behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the part of human factors, Wu and Xu [21] and Abele et al [22] highlighted that driver behaviors such as speeding, drunk-driving, fatigue, safety measures adopted, and risktaking behaviors are the most influential causes of traffic-related causalities. Febres et al [23] blamed young drivers for risky driving behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Obeid et al [25] used a driving simulator to analyze driver-pedestrian interaction from the driver's perspective and concluded that a driver's aggression is affected by approach velocity, curbside parking, crosswalks, and the number of pedestrians crossing the street. � Abele et al [26] compared young drivers' interaction behavior with child and adult pedestrians. ey found that curb extension was the most efficient safety measure that led to the most appropriate driving speed at pedestrian crossings [27].…”
Section: Human-in-the-loopmentioning
confidence: 99%
“…An important aspect here is that road users' decisions on what interactive behaviours to adopt are clearly affected by the specifics of the traffic environment in question, as interpreted against the backdrop of the previously discussed shared reference frame, or common ground, of the interacting road users. Also individual factors such as gender and age matter in this respect (Plumert, Kearney, and Cremer 2007;Ābele, Haustein, and Møller 2018;Lobjois, Benguigui, and Cavallo 2013), as do factors related to human attention or capacity limitations, and secondary tasks and distractions (Janouch et al 2018;Thompson et al 2013;Ljung Aust, Fagerlind, and Sagberg 2012;Choudhary and Velaga 2017).…”
Section: Relationship Of the Framework To Existing Theoretical Perspementioning
confidence: 99%